Promotive and preventive programs about basic life support in Medan Barat district - Lubis, Bastian; Amelia, Putri; Nafiah Nasution, Ali; Silvanni Nasution, Melati; Nasution, Silvanni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Cardiac arrest remains a prominent public health problem and cause of death globally. Despite there is no national data of Indonesia available currently, around 350,000 people in the United States and Canada experienced an arrest every year, and half of them were dead. The community knowledge and awareness about basic life support, particularly among mothers, is still low. Therefore, they cannot contribute effectively in providing first-aid to reduce the mortality. To improve this situation, we need an education and training program about basic life support for the PKK mothers and Posyandu cadres in West Medan to reduce the mortality rate of cardiac arrest in Indonesia. The activity was conducted in several stages, from basic data collection, lectures, basic life support practical training, evaluation and guidebooks handover. It was attended by 26 people, 15 women (57.7%) and 11 men (42.3%), with a mean age of 39 years old. No significant change was found in the level of knowledge and behavior before and after the activity (Z-score: 0,001; p= 1,000).